NANOPARTICLE TRACKING ANALYSIS OF DIFFERENT CONJUGATED GOLD NANOPARTICLES - Pereira, Beatriz Martins (2023)
Gold nanoparticles, with their unique properties and versatility, have revolutionized fields like medicine and nanotechnology. Bioconjugating gold nanoparticles with molecules like aptamers and DNA origami is crucial for tailoring nanomaterials for specific applications. However, a critical chal-lenge lies in understanding how bioconjugation impacts their properties, like size and stability altera-tions. Additionally, understanding the Brownian motion of nanoparticles in liquid is essential, as it in-fluences their behavior. Investigating how biofunctionalization affects Brownian motion and the diffu-sion coefficient of gold nanoparticles is a vital question. This insight is key to comprehending the dy-namic behavior of bioconjugated nanoparticles in various applications. This study involved the analysis of gold nanoparticles of varying sizes, both with and without bioconjugation. Specifically, 80 and 100 nanometer gold nanoparticles were bioconjugated using the freezing method, employing the IL-6 aptamer and DNA origami. To characterize these nanoparticles, the primary method employed was nanoparticle tracking analysis (NTA), supplemented by three other techniques. Dynamic light scattering (DLS) was used to directly compare hydrodynamic diameter in-formation with NTA, serving to validate and assess the capabilities of both methods. Zeta potential measurements were employed to evaluate solution stability, while UV-VIS spectroscopy provided ad-ditional insights into nanoparticle size. At the study's conclusion, optimization was achieved for solution concentrations and NTA video analysis parameters. The results revealed distinguishable differences in nanoparticle sizes between bio-conjugated and non-bioconjugated nanoparticles, as measured by both NTA and DLS techniques. No-tably, NTA demonstrated a more substantial size difference with lower standard deviations for both bioconjugation cases. Furthermore, it was established that solutions remained stable following biocon-jugation with the IL-6 aptamer, contrasting with the instability observed when bioconjugated with ori-gami DNA. These findings provide valuable insights into the effects of bioconjugation on nanoparticle properties and stability, with NTA proving particularly effective in discerning these variations.